2019 16th IEEE Annual Consumer Communications &Amp; Networking Conference (CCNC) 2019
DOI: 10.1109/ccnc.2019.8651668
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Coordination Protocol for Safer and more Efficient Lane Change for Connected and Autonomous Vehicles

Abstract: In this paper we will explore novel ways of utilizing inter-vehicle and vehicle to infrastructure communication technology to achieve a safe and efficient lane change manoeuvre for Connected and Autonomous Vehicles (CAVs). The need for such new protocols is due to the risk that every lane change manoeuvre brings to drivers and passengers lives in addition to its negative impact on congestion level and resulting air pollution, if not performed at the right time and using the appropriate speed. To avoid this ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the same year, Junho and Lee(2018) designed to perform two-lane transform maneuvers using an explicit model predictive controller, mainly used for discrete time linear time-varying, and has been shown to be effective in autonomous driving situations. In 2019, Hodgkiss et al(2019) proposed two new complementary protocols for autonomous vehicles to realize efficient and safe lane switching operations for autonomous vehicles.…”
Section: Autonomous Vehicle (B) Situation2mentioning
confidence: 99%
“…In the same year, Junho and Lee(2018) designed to perform two-lane transform maneuvers using an explicit model predictive controller, mainly used for discrete time linear time-varying, and has been shown to be effective in autonomous driving situations. In 2019, Hodgkiss et al(2019) proposed two new complementary protocols for autonomous vehicles to realize efficient and safe lane switching operations for autonomous vehicles.…”
Section: Autonomous Vehicle (B) Situation2mentioning
confidence: 99%
“…Autonomous vehicles undertaking co-operative lane changing using coordination protocols could provide a safer and more efficient lane changing manoeuvre [51]. Researchers have agreed that optimised lane-changing manoeuvres in conjunction with smaller headway gap between trailing ConFAVs have the potential to significantly reduce congestion [52].…”
Section: Lane Changing Behaviour and Congestionmentioning
confidence: 99%
“…In the simulations made with the proposed collaborative lane change model, it has been observed that the vehicles can safely perform the lane change maneuver. Hodgkiss et alHodgkiss et al, (2019) discuss two new methods of utilizing vehicle communication for CAVs to perform lane change maneuvers under high efficiency and high safety. The first method is the method in which the lane change maneuver is performed by giving special permissions to the vehicle that will change lanes of the central management, which includes intelligent transportation systems such as RSU and traffic light controllers throughout a certain distance.…”
mentioning
confidence: 99%